Optimal Electrospun TiO2 Nanofiber Photocatalytic Performance via Synergistic Morphology and Particle Crystallinity with Anatase/Rutile Phase Tuning. Issue 16 (15th May 2019) - Soo, Joshua Zheyan; Lee, Kian Mun; Ang, Bee Chin; Ong, Boon Hoong
Abstract : TiO2 nanofiber photocatalysts offer a highly efficient and stable method of dye degradation through photogenerated radicals. Through electrospinning, the synthesis of the nanofibers with high surface area (i.e., low fiber diameter) and particle crystallinity (e.g., crystallite size and crystal phases) is highly desired to yield the best degradation performance. In this study, it is demonstrated that a synergistic combination of low fiber diameter, high crystallite size, and mixed anatase/rutile ratio is obtained to yield an optimal methylene blue degradation rate constant of 0.04100 min −1 . The optimization is conducted with the aid of response surface analysis of electrospinning parameters (flow rate, applied voltage, and tip‐to‐collector distance (TCD)) toward the obtained fiber diameter response. The nanofiber diameter is observed to be from 177.3 to 310.4 nm across the studied range of parameters. The change in nanofiber diameter exhibits linear relationship with the applied voltage while quadratic relationships are observed for both solution flow rate and TCD. Through selective comparison, the lowering of fiber diameter has an adverse effect on the crystallinity and phase transformation (anatase‐rutile) of TiO2 particles. This relationship is shown to have a significant effect on the photocatalytic performance of the TiO2 nanofibers. Abstract : In this paper, the optimization of the TiO2 nanofiber diameter is conducted by tuning three electrospinning parameters (solution flow rate, applied voltage, and tip‐to‐collector distance). Apart from the fiber diameter, the optimization process has also changed the fiber's surface area and crystalline properties. These changes have an effect on the photocatalytic performance of the nanofibers.